2018
DOI: 10.1039/c8sm00305j
|View full text |Cite
|
Sign up to set email alerts
|

Negative normal stress differencesN1N2in a low concentration capillary suspension

Abstract: Here, negative normal stress differences are reported in capillary suspensions, i.e. particle suspensions in a two-fluid system that creates strong capillary attractions, at a solid concentration of 25%, and a volume fraction that has heretofore been considered too low to show such normal stress differences. Such capillary suspensions have strong particle networks and are shear thinning for the entire range of shear rates studied. Capillary suspensions exist in two states: a pendular state when the secondary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Indeed, the yield stress of PMMA-glycerol-paraffin oil based capillary suspensions in the capillary state are reported to be in the same order of the NP3 in silicone oil normal suspension, indicating a weak attractive capillary force [26]. In this previous work, no apparent yield stress is reported for the PMMA in glycerol normal suspension, which justifies the assumption that no attractive van der Waals force acts on the particles.…”
Section: Capillary Statementioning
confidence: 56%
See 1 more Smart Citation
“…Indeed, the yield stress of PMMA-glycerol-paraffin oil based capillary suspensions in the capillary state are reported to be in the same order of the NP3 in silicone oil normal suspension, indicating a weak attractive capillary force [26]. In this previous work, no apparent yield stress is reported for the PMMA in glycerol normal suspension, which justifies the assumption that no attractive van der Waals force acts on the particles.…”
Section: Capillary Statementioning
confidence: 56%
“…The details of each sample used in this work are given in Table 1. The method of sample preparation for each model system was described in Natalia et al [26]. and all reported measurements were executed at least three times to check their reproducibility.…”
Section: Capillary Suspensionsmentioning
confidence: 99%
“…Capillary suspensions, on the other hand, dry very differently, as depicted in Figure 5b. Previous studies of pendular state capillary suspensions using confocal microscopy have shown that the secondary fluid creates bridges between two particles or, if the amount of liquid is higher, funicular clusters [26,[34][35][36]. In a consolidated coating, this corresponds to the secondary fluid being located at the throats of porous media.…”
Section: Discussionmentioning
confidence: 98%
“…During flow of pendular state suspensions, isolated clusters, present at high shear rates, follow Jeffery orbits giving rise to a positive normal stress difference N 1 − N 2 . As the shear rate is decreased, these clusters collide and begin to align with the flow to form vorticity rolls, resulting in a negative normal stress difference N 1 − N 2 [38]. The magnitude of this stress difference, however, depends on the ability of the flocs to reorientate in the flow, and the pendular state clusters with small bridges show a more negative N 1 − N 2 than the more rigid clusters with higher secondary fluid volumes and coalesced bridges.…”
Section: Yielding Transition and Nonlinear Propertiesmentioning
confidence: 99%